The Influence of Promotion Perception and Investment Perception on Virtual Assets of Mobile Legend Game - Khairi, Muhammad Dahlan; Alamsyahbana, Muhammad Isa; Fauzi; Kurnia, Sri; Utami, Ranti (Indonesian Scientific Publication, 2025)
This study aims to analyze the influence of promotion perception and investment perception on increasing the value of virtual assets in the Mobile Legends game, focusing on STIE Pembangunan Tanjungpinang students as the research object. Using a quantitative approach and primary data collected through a questionnaire of 42 questions to 83 respondents with a purposive sampling technique based on the Slovin formula, the data was analyzed using JASP version 0.19.2 through data quality testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results of the study indicate that partially and simultaneously, promotion perception and investment perception have a significant effect on players' decisions to purchase virtual assets such as skins and heroes. Promotion perception has been shown to increase player awareness and interest, while investment perception drives resource allocation in purchasing digital assets. These two variables together explain most of the variation in virtual asset purchasing decisions, although there are still other factors that influence them.